L' immortalité en ce jardin !: Immortalité humaine et bioéthique : la condition de mortel est-elle vraiment d'ordre public ? - Le Pluard, Quentin (Journal international de bioéthique et d'éthique des sciences, 2024)
Could resource limitation legaly justify human mortality? Schematically, there are two positions on the matter: bioconservatism and neo-Malthusianism on the one hand, transhumanism and cornucopianism on the other, respectively symbolized by ambrosia, exclusively divine food, and the cornucopia, faith in abundance offered to men, in particular thanks to the progress of science. Between the two options, French law and the laws of bioethics allow some guidelines of thought.